2021
DOI: 10.1155/2021/3734252
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Redox Biomarkers in Insulin Resistance: Preclinical Studies in an Animal Model

Abstract: Insulin resistance (IR) is a condition of impaired tissue response to insulin. Although there are many methods to diagnose IR, new biomarkers are still being sought for early and noninvasive diagnosis of the disease. Of particular interest in laboratory diagnostics is saliva collected in a stress-free, noninvasive, and straightforward manner. The purpose of the study was to evaluate the diagnostic utility of salivary redox biomarkers in preclinical studies in an animal model. The study was conducted on 20 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The authors showed an impairment in antioxidant barriers and in ROS scavengers both in plasma and in saliva, proven by the reduction in superoxide dismutase, ascorbic acid and glutathione (GSH) levels in IR mice. 158 These alterations were paralleled by strengthened lipid/protein oxidation and advanced glycation end products in both biological fluids, showing an elevated coefficient of correlation between the two.…”
Section: Salivary Biomarkers Of Inflammationmentioning
confidence: 95%
“…The authors showed an impairment in antioxidant barriers and in ROS scavengers both in plasma and in saliva, proven by the reduction in superoxide dismutase, ascorbic acid and glutathione (GSH) levels in IR mice. 158 These alterations were paralleled by strengthened lipid/protein oxidation and advanced glycation end products in both biological fluids, showing an elevated coefficient of correlation between the two.…”
Section: Salivary Biomarkers Of Inflammationmentioning
confidence: 95%
“…Tobacco is an exogenous origin of ROS [ 14 ]. In diabetic patients, the resistance to insulin causes a decrease in antioxidants and, as a response to the system, ROS concentration increases [ 74 ]. In cardiovascular disease, it was seen an association with periodontitis.…”
Section: The Role Of Ros In Periodontal Diseasementioning
confidence: 99%
“…For example, salivary GSH and 4-hydroxynonenal (4-HNE), products of lipid peroxidation, can be potential biomarkers to measure the degree of systemic oxidative stress in patients with insulin resistance, although additional validation is needed to confirm their diagnostic efficacy [221]. Advanced oxidation protein products (AOPPs), oxidized free cysteine, tumor necrosis factor receptor-1 (TNFR1), and osteopontin are promising biomarkers associated with the loss of estimated glomerular filtration rate (eGFR) in immunoglobulin A (IgA) nephropathy, a kidney disease also known as Berger's disease.…”
Section: Evaluation Tools For Mitochondrial Health Statusmentioning
confidence: 99%